DUSP1 and DUSP6 : The novel therapeutic targets in drug-resistant HER2+ breast cancer - Tienhaara, Mari (My University, 2021)
The human epidermal growth factor receptor 2 (HER2) is overexpressed and/or amplified in 15-20% of breast cancer patients and associates with a poor survival. Most patients with HER2+ breast cancer develop resistance to HER2 inhibitors and therefore it is important to elucidate the mechanisms underlying HER2 therapy resistance. HER2 signaling regulates several mitogen-activated protein kinases (MAPKs) which are inactivated by the oncogenic dual speciﬁcity phosphatases (DUSPs). The DUSPs play key roles in tumor initiation, malignant progression, and therapy resistance, and in this regard, a better understanding of the roles of the DUSPs in resistance to HER2 inhibitors will open new windows of therapeutic opportunities. My project aimed to find out whether inhibition of DUSP1 and DUSP6 has anti-tumor activity in drug-resistant HER2+ breast cancer cells. Treatment of these cells with a DUSP1 & 6 inhibitor, BCI, reduced their viability, and synergistically increased their sensitivity to the HER2 inhibitors lapatinib and neratinib. These findings were confirmed by siRNA-mediated knockdown and CRISPR-mediated knockout of the DUSPs. Moreover, knockdown of DUSP6 decreased HER2 & HER3, implying DUSP6-mediated regulation of these important receptor tyrosine kinases in HER2+ breast cancer cells. Taken together, these findings suggest that the DUSPs are potentially attractive therapeutic targets in drug-resistant HER2+ breast cancer cells. More in-depth in vivo investigations are required to reveal the contribution of the DUSPs to resistance to HER2-directed therapies in breast cancer.
Keywords: HER2+ breast cancer, resistance, DUSP1, DUSP6